Tailoring International Pronunciation Activities for Hungarian Learners of English - Gyurka, Noémi; Piukovics, Ágnes (Research in Language, 2023)
Pronunciation teaching is gaining more and more recognition in international contexts, however, empirical research concerning pronunciation teaching is underrepresented in the Hungarian educational context. While there are a few studies that briefly touch upon the learners’ attitudes towards pronunciation, there is limited data concerning the ways in which pronunciation could be integrated into the Hungarian English as a foreign language (EFL) classroom. Therefore, to narrow down the gap, this paper aims to investigate how international pronunciation activities could be modified when teaching Hungarian learners specifically, and how these activities could be integrated successfully into the classroom. The case study conducted involved 13 learners, who were taught by the first author of the paper as the teacher-researcher. The timeframe of the research was 11 weeks, throughout which altogether five pronunciation activities were tailored and integrated into the lessons. The results indicate that taking only methodological considerations when deciding on what feature to teach was not sufficient for successful integration. It was concluded that the learners needed to be aware of the goals of the task, its relevance to their development, and most importantly, they had to be motivated and in turn engaged, as all the factors mentioned above are prerequisites of successful integration.